2017
DOI: 10.1017/s0033291717002173
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 (NRG1) polymorphisms linked with psychosis transition are associated with enlarged lateral ventricles and white matter disruption in schizophrenia

Abstract: Our findings build on a growing body of research supporting the functional importance of genetic variation within the NRG1 gene and complement previous findings implicating the rs4281084 and rs12155594 SNPs as markers for psychosis transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A recent study indicated that mice with a subtle defect of myelination could exhibit the schizophrenia-like symptoms (31). In the past decade, there is growing evidence from imaging (32), genetic (33, 34), and postmortem (35, 36) studies that white matter impairment plays an important role in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that mice with a subtle defect of myelination could exhibit the schizophrenia-like symptoms (31). In the past decade, there is growing evidence from imaging (32), genetic (33, 34), and postmortem (35, 36) studies that white matter impairment plays an important role in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling deficits in NRG1/ErbB3 has been identified in schizophrenia patients ( Corfas et al, 2004 ). Single nucleotide polymorphisms in NRG1; have been associated with psychosis and enlarged lateral ventricles and white matter disruption in schizophrenia ( Bousman et al, 2018 ). Another important mediator between microglia and neuron communication is BDNF, where microglia is one of the central source of BDNF ( Ferrini and De Koninck, 2013 ).…”
Section: Schizophreniamentioning
confidence: 99%
“… 36 It has been linked to NRG1 risk variants in first-episode schizophrenia patients 37 and in individuals at high risk for psychosis. 38 We reported enlarged lateral ventricles in transgenic mice with CRD-NRG1 overexpression. 14 Here, we confirm increased ventricular size in T-Nrg1 mice, demonstrating ventricular enlargement as a specific outcome of hyperactive CRD-NRG1 signaling.…”
Section: Discussionmentioning
confidence: 79%